An integrated analysis of the efficacy and safety of desvenlafaxine in the treatment of major depressive disorder. (May 2016) - Carrasco, José L.; Kornstein, Susan G.; McIntyre, Roger S.; Fayyad, Rana; Prieto, Rita; Salas, Maribel; Mackell, Joan; Boucher, Matthieu
Abstract : The chronic course of major depressive disorder (MDD) often impedes the ability of patients to achieve full remission. Return of full functioning is a critical goal of antidepressant pharmacotherapy as the presence of residual depressive symptoms is associated with an increased risk of relapse. Treatment guidelines recommend selective serotonin reuptake inhibitors, serotonin–norepinephrine reuptake inhibitors, or atypical antidepressants as first-line treatment for moderate to severe MDD. Desvenlafaxine, administered as desvenlafaxine succinate, is an serotonin–norepinephrine reuptake inhibitor approved for the treatment of adults with MDD at the recommended dose of 50 mg/day. The aim of this integrated analysis was to assess the efficacy and safety of desvenlafaxine 50 and 100 mg/day compared with placebo in adult outpatients with MDD. The analysis used data from nine fixed-dose, short-term, placebo-controlled studies in adult outpatients diagnosed with MDD who had depressive symptoms for at least 30 days. Data from 4279 and 4317 patients were pooled for the efficacy and safety analyses, respectively. Statistically significant improvements were observed with desvenlafaxine 50 and 100 mg/day versus placebo for all efficacy endpoints assessed, including improvements in depressive symptoms, response and remission rates, as well as functional and cognitive outcomes. Treatment with desvenlafaxine 50 and 100 mg/day was generally safe and well tolerated. The findings of this integrated analysis of data from a large population of patients with MDD confirmed the antidepressant efficacy of both desvenlafaxine doses and add to previous evidence supporting the efficacy of desvenlafaxine.